Primary caregiver, agent transmitting infections associated to health care: literature review - Blancarte-Fuentes, Enrique (Universidad de Sonora, 2020)
Introduction: Infections associated to health care represent a public health problem, increase costs in medical care, morbidity and mortality. Humans are already identified as risk factors; however, “the caregiver” has scarcely been studied, and he can be a reservoir and transmitter of one or several infections. Objective: investigate into the current scientific evidence related to common infections, risk factors, knowledge, practice, and aptitude of the caregiver and his relationship with the infections associated to health care. Methodology: Systematic review of literature carried out based on electronic data, namely, Pub-Med, BVS, Trip Database, Science Direct, Ebsco Host, and Google Scholar. Documents published from 2013 to 2018, in English, Portuguese, and Spanish, were assessed; the terms MESH and DeCs, “nosocomial infection”, “epidemiology”, “caregivers”, and “patient care” were used. A PICO question was raised, the studies selected included meta-analysis, randomized and controlled clinical trials, systematic revisions, and qualitative studies. Exclusion criteria were comprised by studies that included caregivers at home and in intensive care units, both for adults and children. Results and conclusions: 419 articles were obtained; 15 of them met the inclusion criteria, which showed the type of infections that are most common, as well as risk factors, knowledge, practices, and aptitudes of the caregivers in the prevention of IAAS (health-care associated infections) (by its acronym in Spanish), concluding that there is little scientific evidence, and deficiencies in knowledge, programs, and interventions addressed to the caregiver to prevent IAAS.